Control and estimation techniques applied to smart microgrids: A review. (June 2023) - Mbungu, Nsilulu T.; Ismail, Ali A.; AlShabi, Mohammad; Bansal, Ramesh C.; Elnady, A.; Hamid, Abdul Kadir
Abstract: The performance of microgrid operation requires hierarchical control and estimation schemes that coordinate and monitor the system dynamics within the expected manipulated and control variables. Smart grid technologies possess innovative tools and frameworks to model the dynamic behaviour of microgrids regardless of their types, structures, etc. Various control and estimation technologies are reviewed for developing dynamic models of smart microgrids. The hierarchical system of a microgrid control consists of three architectural layers, primary, secondary and tertiary, which need to be supported by real-time monitoring and measurement environment of the system variables and parameters. Various control and estimation schemes have been devised to handle the dynamic performance of microgrids in the function of control layers requirement. Firstly, control schemes in the innovative grid environment are evaluated to understand the dynamics of the developed technologies. Six control technologies, linear, non-linear, robust, predictive, intelligent and adaptive, are mainly used to model the control design within the layer(s) regardless of the types of microgrids. Secondly, the estimation technologies are evaluated based on the state of variables, locations and modelling of microgrids that can efficiently support the performance of the controllers and operating microgrids. Finally, a future vision for designing hierarchical and architectural control techniques for the optimal operation of intelligent microgrids is also provided. Therefore, this study will serve as a fundamental conceptual framework to select a perfect optimal design modelling strategy and policy-making decisions to control, monitor and protect the innovative electrical network. Graphical abstract: Highlights: Frameworks for optimal control and monitoring of smart power grids are presented. Propose novel control structures as a golden opportunity for autonomous power grid development. Assess the opportunity of modern energy systems for sustainable development goals. Develop a digital thread framework for digital twin designs of a modern power grid. Provide challenges and future perspectives for autonomous power grid technologies.